2022
DOI: 10.35808/ijeba/754
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Factors Affecting Tax Evasion in Greece

Abstract: Purpose: This study is an attempt to capture the concept of tax evasion, to distinguish it from tax avoidance and to illustrate the magnitude of the problem in Greece. Design/Methodology/Approach: Time series analysis and regression analysis were performed to determine which factors affect tax compliance in Greece. Data were collected from three different directorates of the Greek Independent Authority for Public Revenue (IAPR), K.E.ME.EP. (Audit Authority for Large Enterprises), K.E.F.O.ME.P. (Audit Authorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In addition, they assessed the effectiveness of measures taken to curb corruption as presented in Table 7 below, according to which 84.10% consider "direct accountability", 81.90% consider "equal application of laws & administration of justice without delay", 76.70% consider "reduction of bureaucracy" and 76.50% consider "improvement of control mechanisms" to be most effective. Kounadeas et al (2022) also indicated the importance of audits in fighting tax evasion/corruption. Ploumi (2014) had reported "equal application of laws & administration of justice without delay", followed by "e-governance/digitalization" and "stricter penalties".…”
Section: Main Findingsmentioning
confidence: 99%
“…In addition, they assessed the effectiveness of measures taken to curb corruption as presented in Table 7 below, according to which 84.10% consider "direct accountability", 81.90% consider "equal application of laws & administration of justice without delay", 76.70% consider "reduction of bureaucracy" and 76.50% consider "improvement of control mechanisms" to be most effective. Kounadeas et al (2022) also indicated the importance of audits in fighting tax evasion/corruption. Ploumi (2014) had reported "equal application of laws & administration of justice without delay", followed by "e-governance/digitalization" and "stricter penalties".…”
Section: Main Findingsmentioning
confidence: 99%
“…The present study highlights challenges in revenue collection, including a poor administrative capacity, tax evasion, corruption, and political pressure. Kounadeas et al (2022) analyze the factors affecting tax evasion in Greece. Martinez (2015) emphasizes the significance of accountability and good governance in managing local government revenues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Payment by electronic means is recorded and it is easy to cross-check the revenues of businesses. Therefore, the more business revenues are derived from electronic payments, the more the likelihood of tax evasion is reduced (Kounadeas et al, 2022). Brockmeyer and Saenz Somarriba (2022) investigated whether the digitisation of transactions in an economy increases tax revenues and generally improves citizens' compliance with the tax system.…”
Section: Literature Overviewmentioning
confidence: 99%
“…It is a phenomenon that hinders economic prosperity and growth, and therefore efforts are being made to reduce it (McGee, 2011). Particularly in the case of Greece, tax evasion is a major issue that has been plaguing the Greek economy for decades and has a significant impact on entrepreneurship and growth (Vousinas, 2017;Balios et al, 2020;Kounadeas et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation